Mutant membrane protein of the budding yeast spindle pole body is targeted to the endoplasmic reticulum degradation pathway. - McBratney, Susan (2002)
Mutation of either the yeast MPS2 or the NDC1 gene leads to identical spindle pole body (SPB) duplication defects: The newly formed SPB is improperly inserted into the nuclear envelope (NE), preventing the cell from forming a bipolar mitotic spindle. We have previously shown that both MPS2 and NDC1 encode integral membrane proteins localized at the SPB. Here we show that CUE1, previously known to have a role in coupling ubiquitin conjugation to ER degradation, is an unusual dosage suppressor of mutations in MPS2 and NDC1. Cue1p has been shown to recruit the soluble ubiquitin-conjugating enzyme, Ubc7p, to the cytoplasmic face of the ER membrane where it can ubiquitinate its substrates and target them for degradation by the proteasome. Both mps2-1 and ndc1-1 are also suppressed by disruption of UBC7 or its partner, UBC6. The Mps2-1p mutant protein level is markedly reduced compared to wild-type Mps2p, and deletion of CUE1 restores the level of Mps2-1p to nearly wild-type levels. Our data indicate that Mps2p may be targeted for degradation by the ER quality control pathway.